A cream pie with rat poison. La Madone in the Netherlands - Erica van Boven; Mathijs Sanders (Relief: Revue Électronique de Littérature Francaise, 2015)
Shortly after the publication of La Madone des sleepings in 1925, Maurice Dekobra became a household name among Dutch readers and critics. By mapping the critical reception of Dekobra’s novel in the Netherlands, this article explores the attitudes of Dutch journalists and critics towards popular French literature during the interwar period. Which conceptions of literature and culture were involved and which institutional interests were at stake? What does the reception of Dekobra reveal about the conditions of the Dutch literary field?